2014
DOI: 10.2478/10004-1254-65-2014-2449
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of soil cyanide by single and mixed cultures of Pseudomonas stutzeri and Bacillus subtilis

Abstract: Summary The aim of this investigation was to study whether certain bacteria could be used for cyanide degradation in soil. The bacteria Pseudomonas stutzeri and Bacillus subtilis were selected based on their good growth in a minimal medium containing 0.8 mg mL-1 potassium cyanide (KCN). In this study we tested their ability to reduce cyanide levels in a medium containing 1.5 mg mL-1 of KCN. Although both microorganisms reduced cyanide levels, Pseudomonas stutzeri was the more effective test organism. Later on,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…In literature, cyanide containing soil samples are generally treated by phytoremediation agents such as Sorghum bicolor, Linum usitassium [34], Eichornia crassipes [35], Salix babylonica [36] and Zea mays [37]. In parallel with our research, in another study it is found that Bacillus subtilis and Pseudomonas stutzeri degraded cyanide in soil (0.218 mg/g cyanide/soil) with the percentages of 66.9% and 72% in 10 days, respectively [38]. In this respect, K. oxytoca culture and sterile crude extract may be used in bioremediation of cyanide in contaminated areas too.…”
Section: Resultssupporting
confidence: 84%
“…In literature, cyanide containing soil samples are generally treated by phytoremediation agents such as Sorghum bicolor, Linum usitassium [34], Eichornia crassipes [35], Salix babylonica [36] and Zea mays [37]. In parallel with our research, in another study it is found that Bacillus subtilis and Pseudomonas stutzeri degraded cyanide in soil (0.218 mg/g cyanide/soil) with the percentages of 66.9% and 72% in 10 days, respectively [38]. In this respect, K. oxytoca culture and sterile crude extract may be used in bioremediation of cyanide in contaminated areas too.…”
Section: Resultssupporting
confidence: 84%
“…Many metabolic capabilities such as degradation of aromatic compounds [33][34][35][36][37] , denitrification , and nitrogen fixation 38 have been identified in different strains of this species. Various strains of P. stutzeri have been used in biotechnological processes such as biocatalysis production of pyruvate 39 and 2-oxobutyrate 40, 41 , water quality control 42 and degradation of soil cyanide 43 . The entire genome sequence of Pseudomonas stutzeri A1501 has been published in 2008 44 .…”
Section: Pseudomonas Stutzeri and Its Metabolismmentioning
confidence: 99%
“…They demonstrated that cyanide played a role as a substrate until 300 ppm in which the mixture recorded maximum growth rate and cyanide removal. Nwokoro and Dibua [32] examined the degradation of cyanide by single and mixed culture of Pseudomonas stutzeri and Bacillus subtilis, and they reported that P. stutzeri, B. subtilis and their mixture removed cyanide up to72, 66.9 and 88.5%, respectively.…”
Section: Removal Efficiency Of Mixed Culturementioning
confidence: 99%